Noninvasive positive-pressure ventilation for children with acute asthma: a meta-analysis of randomized controlled trials - Dai, Jiajia; Wang, Libo; Wang, Fang; Wang, Lu; Wen, Qingfen (Frontiers in Pediatrics, 2023)
Background: Noninvasive positive-pressure ventilation (NPPV) can be effective in children with acute asthma. However, clinical evidence remains limited. The objective of the meta-analysis was to systematically assess NPPV's effectiveness and safety in treating children with acute asthma. Methods: Relevant randomized controlled trials were obtained from electronic resources, including PubMed, Embase, Cochrane’s Library, Wanfang, and CNKI databases. The influence of potential heterogeneity was taken into account before using a random-effect model to pool the results. Results: A total of 10 RCTs involving 558 children with acute asthma were included in the meta-analysis. Compared to conventional treatment alone, additional use of NPPV significantly improved early blood gas parameters such as the oxygen saturation (mean difference [MD]: 4.28%, 95% confidence interval [CI]: 1.51 to 7.04, p=0.002; I2 =80%), partial pressure of oxygen (MD: 10.61mmHg, 95% CI: 6.06 to 15.16, p<0.001; I2 =89%), and partial pressure of carbon dioxide (MD: -6.29mmHg, 95% CI: -9.81 to -2.77, p<0.001; I2 =85%) in the arterial blood. Moreover, NPPV was also associated with early reduced respiratory rate (MD: -12.90, 95% CI: -22.21 to -3.60, p=0.007; I2=71%), improved symptom score (SMD: -1.85, 95% CI: -3.65 to -0.07, p=0.04; I2 =92%), and shortened hospital stay (MD: -1.82 days, 95% CI: -2.32 to -1.31, p<0.001; I2=0%). No severe adverse events related to NPPV were reported. Conclusions: NPPV in children with acute asthma is associated with improved gas exchange, decreased respiratory rates, a lower symptom score, and a shorter hospital stay. These results suggest that NPPV may be as effective and safe as conventional treatment for pediatric patients with acute asthma.